2018
DOI: 10.3390/su10124760
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration between Heterogeneous Practitioners in Sustainability Research: A Comparative Analysis of Three Transdisciplinary Programmes

Abstract: There is wide agreement about the importance of transdisciplinary research to address complex sustainability issues. Although there is a growing body of literature about the management of transdisciplinary research programmes as well as the challenges relating to the collaboration between academic researchers and practitioners, empirical research has to date paid little attention to the challenges related to the variation of practitioners involved in these programmes. This paper presents a comparative analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…If addressed at all, much of the coproduction literature offers recommendations to ensure good processes, for example about importance of trust and open communication [47,48], which fail to address power and politics of these complex issues, including a neglect of how the results will feed into formal politized decisionmaking structures. Other literature emphasizes the importance of making the 'right' connections between researchers, decision-makers and representatives of stakeholder groups, to ensure inclusivity and representativeness, and the need to develop a vocabulary and skills for bridging diverse boundaries [49][50][51][52][53]. This focus on new connections, language and skills often does not reflect on the socio-cultural biases in the co-production process, and the potential harm (for example the loss of particular political interests, norms and values in the co-production process) that can result from attempts to realise these values and conditions.…”
Section: Depoliticizationmentioning
confidence: 99%
“…If addressed at all, much of the coproduction literature offers recommendations to ensure good processes, for example about importance of trust and open communication [47,48], which fail to address power and politics of these complex issues, including a neglect of how the results will feed into formal politized decisionmaking structures. Other literature emphasizes the importance of making the 'right' connections between researchers, decision-makers and representatives of stakeholder groups, to ensure inclusivity and representativeness, and the need to develop a vocabulary and skills for bridging diverse boundaries [49][50][51][52][53]. This focus on new connections, language and skills often does not reflect on the socio-cultural biases in the co-production process, and the potential harm (for example the loss of particular political interests, norms and values in the co-production process) that can result from attempts to realise these values and conditions.…”
Section: Depoliticizationmentioning
confidence: 99%
“…According to the states of the framework for Responsible Innovation, people in the innovation process should be mutually responsive to each other and strive for a bottom-up-policy; including members of the wider public, and appreciate the quality of dialogue between different stakeholders as a learning exercise [38]. Hessels et al [4] add to this position by suggesting that people without a scientific background should be involved in research and development, which is defined as transdisciplinarity: "There is wide agreement about the importance of transdisciplinary research to address complex sustainability issues" and the merits of participation [13,39], although the "paradoxes of participation" [40] are also discussed critically in the literature [40,41].…”
Section: Inter-and Transdisciplinary Approaches In Transport Sciencementioning
confidence: 99%
“…The discussion on new mobility concepts is usually carried out from a very technical perspective [1,2]. However, when dealing with complex transformation processes of socio-technical systems, like the transport system, we are not only confronted with technical challenges but also with questions of user acceptance, which include the users' willingness and ability to change long established behavioral patterns [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the institutional level, transdisciplinary research has been shown to be less rewarding in terms of publications in high impact journals (Rafols et al 2012) career advancement (Van Rijnsoever and Hessels 2011), and funding acquisition (Bromham et al 2016). Strategies to overcome the various challenges include balanced team composition (Boon et al 2014), smart programme design (Hessels et al 2018) and tailored quality criteria (Jahn and Keil 2015). The current paper deals with the struggles of individual researchers in dealing with the demands and expectations of different actors.…”
Section: Transdisciplinarity and Sustainability Programmesmentioning
confidence: 99%